Do I Dare to Leave the Universe Alone? Environmental Crisis, Narrative Identity, and Collective Agency in Contemporary Young Adult Fiction - Jonas Vanhove; Simon De Backer (Humanities)
Narrative identity, or the construction of a coherent life story to shape a sense of self, is a crucial aspect of identity formation. Narrative identity is impacted by the prevailing cultural narratives during the period of adolescence. This article, drawing on theory from literary studies and sociology, explores the impact of cultural narratives of environmental crisis and destruction on an emerging narrative identity in adolescents as represented in young adult literature. The selected novels—Dry by Neal and Jarrod Shusterman, Green Rising by Lauren James, and Snowflake, AZ by Marcus Sedgwick—examine their protagonists’ agency and transformational potential. They foreground collective agency and human–nonhuman assemblages as possible responses to environmental crisis. Although two novels (Dry, Green Rising) affirm that narratives of environmental destruction engage the transformational potential of adolescents for society, the third novel (Snowflake, AZ) complicates this image and questions whether the impact of narratives of environmental crisis could be too overwhelming for adolescents to bear. The article concludes that the young adolescent protagonists adapt their narrative identity in response to environmental destruction.